Voice or public sector management? An empirical investigation of determinants of public sector performance based on a survey of public officials - Daniel Kaufmann; Gil Mehrez; Tugrul Gurgur (Journal of Applied Economics, 2019)
Drawing on an in-depth governance micro-survey of public officials in Bolivia, we address empirically the question of the relative importance of the various determinants of governance. We find that commonly made inferences about policy based on simple correlation can be highly misleading due to the high correlation between the various governance determinants, as well as the endogeneity in these variables. We find that undue emphasis may have been given in the previous work to a number of conventional public-sector management variables (such as civil servant wages, internal enforcement of rules, autonomy of agency by fiat, etc.), while undermining the priority of "external" (to public sector management) variables, such as citizen voice and transparency. The latter set of "voice"-related variables has a larger effect on the service delivery performance and corruption than the more traditional public-sector management type of variables.
Keywords: C36; D73; 330; Bolivia; Governance; micro-survey; public sector management; transparency